Perbedaan Durasi Tidur dan Asupan Makan pada Anak Stunting dan Tidak Stunting Usia Sekolah - Yessi Alza; Lidya Novita (Politeknik Kesehatan Tanjung Karang, 2021)
Stunting is a chronic malnutrition problem caused by inadequate nutritional intake for a long time, resulting in growth disorders in children that is height is lower than the standard age. The physical growth of children is greatly influenced by nutritional intake and activity in children. The purpose of this study was to determine the differences in sleep duration and food intake on the incidence of stunting in elementary school children. This was an analytic observational study with a cross-sectional design. This research was conducted in Kecamatan Tampan Sidomulyo Timur in February-August 2019. The sample of this study was 90 elementary school children who met the inclusion criteria. The independent variables in this study were sleep duration, food intake and the dependent variable was stunting. The data collection consists of weighing, height measurement, food recall 2x24 hours to determine the level of food consumption, and interviews by filling out a modified Children's Sleep Habit Questioner (CSHQ) questionnaire. Data analysis used an independent t-test and Mann-Whitney test. The results showed that there was no difference in sleep duration between stunting and non-stunting children (p-value=0,954) and there was a difference in energy and protein intake between stunted and non-stunting children (p-value=0,004 and p-value=0,036). Children who have inadequate protein and energy have a greater risk of stunting. Further researchers need to test the difference in sleep duration between stunted and non-stunted children.